2011
DOI: 10.1200/jco.2011.38.9635
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Treatment: Anticancer, Antisymptom, or End-of-Life Care?

Abstract: REFERENCES 1. Brauch HB, Schroth W, Ingle JN, et al: CYP2D6 and tamoxifen: Awaiting the denouement. J Clin Oncol 29:4589, 2011 2. Stearns V, Johnson MD, Rae JM, et al: Active tamoxifen metabolite plasma concentrations after coadministration of tamoxifen and the selective serotonin reuptake inhibitor paroxetine. J Natl Cancer Inst 95:1758-1764, 2003 3. Johnson MD, Zuo H, Lee KH, et al: Pharmacological characterization of 4-hydroxy-N-desmethyl tamoxifen, a novel active metabolite of tamoxifen. Breast Cancer Res … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…47 Research continues to suggest that the public is ‘death denying’ and that conversation about death and dying remains largely ‘taboo’. 812 Public confusion about end-of-life terminology is unsurprising when set against the background of debate among researchers, practitioners and policymakers about the scope, definitions, goals and approaches of palliative care 13,14 and the changing historical definitions of the term. 2 In the United Kingdom, this situation has been further complicated by recent negative media attention 15,16 about the Liverpool Care Pathway for Dying Patients (LCP) (an internationally recognised best practice model for caring for people in the final days of life).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Research continues to suggest that the public is ‘death denying’ and that conversation about death and dying remains largely ‘taboo’. 812 Public confusion about end-of-life terminology is unsurprising when set against the background of debate among researchers, practitioners and policymakers about the scope, definitions, goals and approaches of palliative care 13,14 and the changing historical definitions of the term. 2 In the United Kingdom, this situation has been further complicated by recent negative media attention 15,16 about the Liverpool Care Pathway for Dying Patients (LCP) (an internationally recognised best practice model for caring for people in the final days of life).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Research continues to suggest that the public is 'death denying' and that conversation about death and dying remains largely 'taboo'. [8][9][10][11][12] Public confusion about end of life terminology is unsurprising when set against the background of debate amongst researchers, practitioners and policy makers about the scope, definitions, goals and approaches of palliative care [13][14] and the changing historical definitions of the term. 2 In the UK this situation has been further complicated by recent negative media attention 15.16 Whilst the LCP is well supported by practitioners (with 90% of doctors agreeing in a recent study that they would be happy to be placed on the pathway if they were dying 17 ) confusion has been generated publically about its role in palliative and end of life care at a time when misunderstandings about the aims of palliative care already exist.…”
Section: Introductionmentioning
confidence: 99%
“…2 I further contributed to studies that showed that endoxifen as a selective estrogen receptor modifier is equipotent with 4-hydroxytamoxifen and that both of these metabolites are 10-fold more potent than native tamoxifen. 2 I further contributed to studies that showed that endoxifen as a selective estrogen receptor modifier is equipotent with 4-hydroxytamoxifen and that both of these metabolites are 10-fold more potent than native tamoxifen.…”
mentioning
confidence: 99%